2007
DOI: 10.1364/oe.15.012680
|View full text |Cite
|
Sign up to set email alerts
|

Models for guidance in kagome-structured hollow-core photonic crystal fibres

Abstract: Abstract:We demonstrate by numerical simulation that the general features of the loss spectrum of photonic crystal fibres (PCF) with a kagome structure can be explained by simple models consisting of thin concentric hexagons or rings of glass in air. These easily analysed models provide increased understanding of the mechanism of guidance in kagome PCF, and suggest ways in which the high-loss resonances in the loss spectrum may be shifted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 14 publications
2
75
0
1
Order By: Relevance
“…To better understand HC-ARF, many theoretical efforts have been implemented, such as low DOS interpretation [27], inhibited coupling between the core mode and the circulating resonances along the glass web [28], radial light confinement by concentric glass rings [29], and overall spatial overlap between the core mode and the glass [30]. However, only qualitative conclusions can be drawn from these models.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand HC-ARF, many theoretical efforts have been implemented, such as low DOS interpretation [27], inhibited coupling between the core mode and the circulating resonances along the glass web [28], radial light confinement by concentric glass rings [29], and overall spatial overlap between the core mode and the glass [30]. However, only qualitative conclusions can be drawn from these models.…”
Section: Introductionmentioning
confidence: 99%
“…Kagome fibers were only fully understood in 2007, when their broadband guidance spectrum was attributed to inhibited coupling (IC) guidance [13]. The structural design of these fibers allows for both a continuum of modes supported by the cladding, as well as modes guided by the hollow core.…”
Section: Hollow-core Photonic Crystal Fibresmentioning
confidence: 99%
“…The structural design of these fibers allows for both a continuum of modes supported by the cladding, as well as modes guided by the hollow core. However, the phase between the core and cladding modes is significantly mismatched, which prevents the leakage of light out of the core [13,17]. PBG fibers, in contrast, use a 2D photonic crystal pattern to produce periodic index modulations in the transverse direction that act as a Bragg grating.…”
Section: Hollow-core Photonic Crystal Fibresmentioning
confidence: 99%
“…Kagome lattices IC HC PCFs sometimes have the discrete symmetry of the core boundary but just with a polygonal shape of the core without a negative curvature of the core boundary. The authors in [Pearce et al, 2007] have shown that the loss behavior of a hollow core fiber with the cladding consisting of concentric glass rings or hexagons explain the qualitative features in the loss curves associated with kagome lattice IC HC PCF. The hollow core photonic band gap fiber with the cladding consisting of concentric glass rings has a continuous rotational symmetry of the core modes and is analogous to solid Bragg fibers [Fevrier et.…”
Section: Complicated Boundary Conditions For the Air Core Mode Of Hc mentioning
confidence: 99%